Toward a critical practice: tracing theory through design - Noonan, Hilary Ann (Kansas State University, 2009)
“Toward a Critical Practice: Tracing Theory Through Design” is an exploration of Elizabeth Meyer’s idea of critical inquiry as a mode and process for professional practice as a landscape architect. Critical practice involves the application of ideas embodied in critical theory as a creative endeavor that is both self-critical and self-renewing. Critical theory is essential in bringing a deeper level of understanding to the design of landscape architecture. Critical practice is the application of critical theory to the understanding of built work and the process of design. Using Meyer’s stated intentions for this design process Noonan develops a personal framework for that process. As the framework develops it rapidly becomes multiple, overlapping, mutually supportive frameworks. Multiple perspectives are gained from using multiple viewpoints represented in theory. The frameworks serve to include the dynamics of change and provide access to a deeper understanding of the interrelatedness of forms and processes inherent to any site or project. Issues of representation become more clear and strategies are identified although this aspect of practice deserves much more attention in the future. Theories, frameworks and sources of knowledge are identified and used to question assumptions and biases, challenge orthodoxies of practice, test ideas, develop written and formal vocabulary and inspire, motivate and guide design work. Ideas and theories used in the framework are related to the formal and textual work of other designers past and present. The framework is tested through application to a design project, which is used as the case study for this paper.
Keywords: critical practice; site-related practice; theory; theory in design; case study; phenomenology; Landscape Architecture (0390)